Estimating disability and quality of life after different degrees of hand and forearm trauma - Marinković, Marija; Janjić, Zlata; Nikolić, Jelena (Vojnosanitetski pregled, 2015)
Background/Aim. Hand injuries comprise up to one fourth of all injuries and require excellent skills and aggressive physical therapy with still a high potential to cause long term physical and functional disability which affects one’s quality of life. The aim of this study was to evaluate disability and quality of life in patients with different degrees of hand and forearm injuries using the two different scoring sistems and to examine the correlation between them. Methods. This retrospective study was performed among patients operated on at our clinic due to acute hand and forearm trauma during the period of two years. Four groups of patients were made according to the Modified Hand Injury Severity Score (MHISS). One year after the treatment, phone interviews were made with those patients to answer to the Disability of Arm Shoulder and Hand (quick-DASH) score for estimating disability and to the World Health Organization Quality of Life BREF (WHOQoL-BREF) score to estimate the quality of life regerding four domains: physical, social, environmental and psychological. Results. Out of 182 patients who satisfied the inclusion criteria, only 60 completely answered to the questionnaires, 46 (17%) men and 14 (23%) women. Most of the patients were in the group with moderate injuries according to the MHISS, followed by the group with major and severe injuries. A weak correlation was found between the MHISS and quick DASH score in the group with minor injuries, compared to no correlation between these parameters in other groups. The lowest quality of life was registered in the physical domain, while the highest in the social one. A negative correlation was found among the four domains of the WHOQoL BREF score and quick-DASH score in all the groups. Conclusion. Severity of hand and forearm injuries does not necessarily correlate with patient’s perception of disability. The quality of life was less affected by severity of injury than by the patient’s perception of disability.